PENYERAPAN TENAGA KERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) AGRIBISNIS DAN NON-AGRIBISNIS (STUDI KASUS: DI KELURAHAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA) - Arther Manueke; Jen Tatuh; Lorraine W. Th. Sondak; Agnes E. Loho (Universitas Sam Ratulangi, 2015)
ABSTRACTArther Manueke. Employment Absorption Micro, Small and Medium Enterprises (SMEs) and Non-Agribusiness Agribusiness (Case study: In the Village Kakaskasen Two North Tomohon sub district) under the guidance of Jen Tatuh as Chairman, Lorraine W.Th. Sondak and Agnes E. Loho as members.SMEs are an important factor in improving the economy of a region. The larger the business field increasingly strategic employment of the business and the development of businesses in an area that is growing is also the area. With the development of the business field will lead to employment and the increased employment will reduce unemployment in the region.The research was conducted in the Village Kakaskasen Two North Tomohon sub district from April to June of 2014 by using primary data and secondary data. Primary data was obtained from interviews with mengguanakan list of questions that had been prepared in advance and secondary data obtained from the relevant department of the Office of Village Kakaskasen Two North Tomohon sub district and the Department of Cooperatives Tomohon. Data processing method used in this research is descriptive method using labor coefficient analysis and presented in tabular form.In the last two years of SMEs in Sub Kakaskasen Two increasing number of business units. Data from the village Kakaskasen Two shows in 2012 recorded 82 business units and in 2013 recorded 209 business units. The results showed that the catering business is a business that is at least employment in agribusiness SMEs, but this business has a higher productivity in SMEs Agribusiness, while the restaurant business is a business that is the highest value of the coefficient of productivity of labor, but it is very small. In the non-agribusiness SMEs labor coefficient highest of soundystem rental business that has the highest coefficient is soundystem rental business however small this business productivity while business hotels, cottages, boarding coefficient value of labor productivity is small but great.Overall agribusiness SMEs have a higher absorption than the non-agribusiness SMEs but non-agribusiness SMEs productivity higher than agribusiness SMEs. Businesses that need attention are catering business and hotel business, cotage, boarding because with little manpower capable of generating significant revenue.